Somatic Mutations in Exon 7 of the TP53 Gene in Index Colorectal Lesions Are Associated with the Early Occurrence of Metachronous Adenoma - Hálková, Tereza; Ptáčková, Renata; Semyakina, Anastasiya; Suchánek, Štěpán; Traboulsi, Eva; Ngo, Ondřej; Hejcmanová, Kateřina; Májek, Ondřej; Bureš, Jan; Zavoral, Miroslav; Minárik, Marek; Benešová, Lucie (Cancers, 2022)
(1) Background: this prospective study was focused on detailed analysis of the mutation heterogeneity in colorectal lesions removed during baseline (index) colonoscopy to identify patients at high risk of early occurrence of metachronous adenomas. (2) Methods: a total of 120 patients after endoscopic therapy of advanced colorectal neoplasia size ≥10 mm (index lesion) with subsequent surveillance colonoscopy after 10-18 months were included. In total, 143 index lesions and 84 synchronous lesions in paraffin blocks were divided into up to 30 samples. In each of them, the detection of somatic mutations in 11 hot spot gene loci was performed. Statistical analysis to correlate the mutation profiles and the degree of heterogeneity of the lesions with the risk of metachronous adenoma occurrence was undertaken. (3) Results: mutation in exon 7 of the TP53 gene found in the index lesion significantly correlated with the early occurrence of metachronous adenoma (log-rank test p = 0.003, hazard ratio 2.73, 95% confidence interval 1.14-6.56). We did not find an association between the risk of metachronous adenomas and other markers monitored. (4) Conclusions: the findings of this study could lead to an adjustment of existing recommendations for surveillance colonoscopies in a specific group of patients with mutations in exon 7 of the TP53 gene in an index lesion, where a shortening of surveillance interval may be warranted.